On the distribution of the second-largest latent root for certain high dimensional Wishart matrices. (1st January 2013) - Iimori, Takayuki; Ogura, Toru; Sugiyama, Takakazu
The distribution of the largest latent root was found by Johnstone (2001) for Wishart distributions with large dimension p – 1, when In this paper, we study the distribution of the second-largest latent root of the covariance matrix when are large and satisfy we shall obtain the approximate distribution of the second-largest latent root, and verify the accuracy of the approximate distribution via a simulation study.